Chamling and English Question Words: A Comparative Stud - Rai, Krishna Bahadur (DMC Journal, 2022)
This study aims to explore the questions words of Chamling and analyze the question words of Chamling and English. For this purpose Chamling and English data related to the question words are used. The comparative and contrastive study of data reveals that the position of question words is different in Chamling—initial, middle, and final—and in English—only initial. The position of Chamling question words contrasts with English question words in interrogative sentence. The finding of study shows that question words are used to ask open questions in both languages.